4x-9=4(x+6)

Simple and best practice solution for 4x-9=4(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9=4(x+6) equation:


Simplifying
4x + -9 = 4(x + 6)

Reorder the terms:
-9 + 4x = 4(x + 6)

Reorder the terms:
-9 + 4x = 4(6 + x)
-9 + 4x = (6 * 4 + x * 4)
-9 + 4x = (24 + 4x)

Add '-4x' to each side of the equation.
-9 + 4x + -4x = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + 0 = 24 + 4x + -4x
-9 = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 = 24 + 0
-9 = 24

Solving
-9 = 24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (5z-4)(1+Z)=0 | | 10+20=-3(6x-10) | | 25z^2+36=0 | | 25+3=8 | | 6x-(3x+4)=8x-24 | | 5(v-6)(-v-1)=0 | | 2y-x^2=3 | | 24a^2+a-15=0 | | x(4x-4)+x(2x-3)=(6x+7)(x+2) | | -7(0.1x+0.4)-1.1=-0.4 | | 4n^2+n-3=0 | | 6+9n=5n+6 | | 2x*10=40 | | x-0.025=341.25 | | 2n+wr=r-5h | | L(d)=41+d | | 2(3x-1)/10=4 | | -3(x+6)+4=5(x+3)+7 | | (2b-6)(3b+18)=0 | | 2Ln(x-5)+9=21 | | -27-6x=3 | | 7x-4=4x-16 | | 3y^2-11=-6 | | (8x-5)=(15x+1) | | 2x-1=4(x-3) | | 27xy^6-8x=0 | | -6n+21=12n-14 | | 6(3T-8)+2(3T-6)= | | n=m-.04 | | (7x+6)+(-8+7)= | | 2(3-x)+5=x | | x^3-4x^2+144=36x |

Equations solver categories